THE IMPACT OF MARKET TIMING ON CAPITAL STRUCTURE: EVIDENCE FROM VIETNAM CONSTRUCTION - Nguyễn Hữu Thao (Tạp chí Khoa học Đại học Đà Lạt)
The purpose of this study is to test how equity market timing affects capital structure from the Initial Public Offering (IPO) perspective. Using Ordinary Least Square (OLS) technique to analyze a data-set of 102 Vietnamese enterprises in the construction industry for the period from 2006 to 2014, we conclude that, in the short-term, the impact of equity market timing on capital structure is relatively low. Whereas, in the long-term, the impact of equity market timing on capital structure is more obvious.